2014
DOI: 10.9734/ajea/2014/6502
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Migrant Remittances on the Output of Arable Crop of Farm Households in South Eastern Nigeria

Abstract: This study investigated the impact of remittances on the output of arable of remittance and non receiving farm households in South Eastern Nigeria. A multi-stage random sampling and purposive sampling technique was used in choosing the sample. The cost route technique was used in data collection. Data collected using structured questionnaire and interview schedules were analyzed using such statistical tools as Z test, regression analysis and Chow's test statistic. The result of data analyses revealed that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
(16 reference statements)
3
6
0
Order By: Relevance
“…The amount of remittances received significantly increased the amount invested in agriculture. The finding supports Akpan et al (2014) and Iheke (2014) claim that remittance increases agricultural productivity and output in Nigeria. Redehegn (2019) averred that remittance improves farmers' income from crop and livestock production in Ethiopia.…”
Section: Determinants Of Agricultural Investment Component Of Remittancesupporting
confidence: 87%
See 1 more Smart Citation
“…The amount of remittances received significantly increased the amount invested in agriculture. The finding supports Akpan et al (2014) and Iheke (2014) claim that remittance increases agricultural productivity and output in Nigeria. Redehegn (2019) averred that remittance improves farmers' income from crop and livestock production in Ethiopia.…”
Section: Determinants Of Agricultural Investment Component Of Remittancesupporting
confidence: 87%
“…The contributions of remittances to the development of migrants' households and communities are well documented. For example, Akpan et al (2014) and Iheke (2014) documented the importance of remittance to agricultural productivity and output in Nigeria; Redehegn (2019) averred that remittances increase crop and livestock income in Ethiopia; Ofuaku (2018) opined that it enhances food security in the rural areas of Nigeria while Olowa et al (2013) found its significant impact on poverty reduction in Nigeria. It is a survival strategy for some households and many others invest their remittances in agriculture and other productive activities (Alarima, 2018;Oketayo and Olaleye, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The result shows that a unit increase in the number of years spent in school by the farmers increased the likelihood of adopting improved rice varieties by 0.018 (1.8%), agrochemicals by 0.053 (5.3%), fertilizer by 0.018 (1.8%), mechanized harvesting by 0.0097 (0.97%), improved nursery by 0.559 (55.9%), timely transplanting by 0.0096 (0.96%), and optimum seed rate by 0.026 (2.6%). According to Iheke (2010), education increases the ability of the farmers to adopt agricultural innovation and hence improve their productivity and efficiency.…”
Section: Factors Affecting Adoption Of Rice Production Technologiesmentioning
confidence: 99%
“…In Nigeria, there have been many studies and publications on remittances, ranging from their effect on economic growth (Agu, 2009;Oduh and Urama, 2012;Iheke, 2012;Ojapinwa, 2012;Ojapinwa and Odekunle, 2013;Odionye and Emerole, 2015); their impact on poverty (Chukwuone, Okpukpara, Amaechina, Enebeli -Uzor and Ivoko, 2007;Ajayi, Ijaiya, Ijaiya, Bello, Ijaiya, and Adeyemi (2009) ;Odozia, Awoyemi and Omonona, 2010;Babatunde and Martinetti, 2011;Olowa and Shittu, 2012); their effect on inequality across rural and urban areas (Fonta, Onyukwu and Nwosu, 2011); their effect on Investment (Ojapinwa and Odekunle, 2013); and their effect on the labour supply (Posso, 2012), amongst others.…”
Section: Study Backgroundmentioning
confidence: 99%